Kajian Biaya Perjalanan Akibat Tundaan Lalu Lintas di Ruas Jalan Hasanuddin Denpasar - Budiarnaya, Putu; Sia Babo Amaral, Adelino; Wismantara, Gusti (Jurnal Ilmiah Telsinas, 2021)
The impact of traffic volume and the presence of side obstacles on the Hasanuddin road section causes travel delays which result in a decrease in travel time and has an impact on the time value of vehicles and Vehicle Operational Costs (BOK) that pass on these roads. The purpose of this study is to analyze the performance of the road and the travel costs that occur with delays caused by side obstacles on Jalan Hasanuddin Denpasar. The calculation of BOK for cars uses the method from the Ministry of Public Works in 2005. Meanwhile, the calculation of BOK for motorcycles adheres to the DLLAJ method for the Province of Bali – PTS Consultant 1999. The results of this study are: 1) The performance of Hasanuddin Road is: Traffic volume during peak hours in the morning 1,470.6 junior high school/hour, the afternoon peak hour is 1,346.4 pcu/hour and the afternoon peak hour is 1,425.1 pcu/hour. The road segment capacity is 2,999.8 pcu/hour at peak hours in the morning, afternoon, and evening. The speed of light vehicles at the peak hour in the morning is 13.66 km/hour, the peak hour in the afternoon is 14.32 km/hour and the peak hour in the afternoon is 12.63 km/hour. The degree of saturation is 0.490 for the morning peak hour, 0.449 for the afternoon peak hour and 0.475 for the afternoon peak hour. 2) Travel costs without traffic delays on Jalan Hasanuddin Denpasar at peak hours in the morning IDR 474,442.79, afternoon IDR 477,814.01, afternoon IDR 474,310.83 with a total amount of 1,426,547.63, then there is a delay on Hansauddin Road, morning peak hours 0.0138 hours, Afternoon 0.0141 hours, afternoon 0.0135, so for Traffic Travel Costs due to traffic delays on Jalan Hasanudin Denpasar it increases at peak hours in the morning, IDR 480,969.82 in the afternoon IDR 484,551.19, afternoon IDR 480,714.02 with an amount of IDR 1,446,235.04 at peak hours